Soft Computing in Data Science First International Conference, SCDS 2015, Putrajaya, Malaysia, September 2-3, 2015, Proceedings - Berry, Michael W.; Hj. Mohamed, Azlinah; Yap, Bee Wah.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the International Conference on Soft Computing in Data Science, SCDS 2015, held in Putrajaya, Malaysia, in September 2015. The 25 revised full papers presented were carefully reviewed and selected from 69 submissions. The papers are organized in topical sections on data mining; fuzzy computing; evolutionary computing and optimization; pattern recognition; human machine interface; hybrid methods.
Keywords: Computer science; Algorithms; Data mining; User interfaces (Computer systems).; Artificial intelligence; Pattern recognition; Computer Science; Data Mining and Knowledge Discovery; Algorithm Analysis and Problem Complexity; Artificial Intelligence (incl. Robotics).; Pattern Recognition; User Interfaces and Human Computer Interaction; Electronic books